The Oxford handbook of early evangelicalism - Yeager, Jonathan (Oxford University Press, 2022)
"Evangelicalism is one of the most popular and diverse religious movements in the world today. Evangelicals can be found on every continent and among nearly all Christian denominations. The origin of this group of people has been traced to the turn of the eighteenth century, with roots in the Puritan and Pietist movements in England and Germany. The earliest evangelicals could be found among Anglicans, Baptists, Congregationalists, Methodists, Moravians, and Presbyterians throughout North America, Britain, and Western Europe, and included some of the foremost names of the age, such as Jonathan Edwards, John Wesley, and George Whitefield. Early evangelicals were abolitionists, historians, hymn writers, missionaries, philanthropists, poets, preachers, and theologians. They participated in the major cultural and intellectual currents of the day, and founded institutions of higher education not limited to Dartmouth College, Brown University, and Princeton University. The Oxford Handbook of Early Evangelicalism provides the most authoritative and comprehensive overview of the significant figures and religious communities associated with early evangelicalism within the contextual and cultural environment of the long eighteenth century, with essays written by the world's leading experts in the field of eighteenth-century studies"--
Includes bibliographical references and index
Keywords: Aufsatzsammlung; Evangelikale Theologie; Evangelikale Bewegung